Maternal satisfaction with postpartum surgical pain management in a hospital in northern Mexico - López España, Julia Teresa (Universidad de Sonora, 2021)
Introduction: The quality of care is a priority in the health system, especially patient satisfaction. Postoperative pain management is an indicator that can affect it. Objective: Establish the relationship between maternal satisfaction with postoperative pain management, pain intensity, preoperative orientation, health personnel response time and obstetric factors in a hospital in northern Mexico. Methodology: Descriptive, correlational design. A total of 259 postpartum surgical patients from a public hospital in Monterrey, Nuevo Leon, Mexico participated. The Patient Pain Intensity Questionnaire was used; women with 24 hours of postpartum surgery were included in the study; women with tubal ligation or hysterectomy were excluded. Descriptive and inferential statistics were used. Results: All participants presented pain; 61.4% reported severe pain in the first 24 hours; 69.5% reported a response time for pain management of less than 10 minutes. Mean satisfaction was 8.9 (SD=1.3). A relationship was found between maternal satisfaction with postoperative pain management and personnel response time (p=.001); as well as with the number of cesarean sections (p=.04). Women who received preoperative counseling reported greater satisfaction with pain management (9 vs. 8.27, p=.001) and less pain (7.87 vs. 6.90, p=.01). Conclusions: Correct pain management should be prioritized as a quality criterion. Preoperative orientation is a practice that should be reinforced in the care of surgical patients.